Jak projektować etnoanimacyjne badania w działaniu. Dobra praktyka i suwak animacyjny - Dobiasz-Krysiak, Maja; Dobiasz-Krysiak, Maja (Studia Etnologiczne i Antropologiczne, 2016)
Ethnoanimation connects ethnographic research and culture animation. This method has been developed for ten years by Tomasz Rakowski, The Field Collective and author of the text. The last project where the method was tested was the laboratory known as the “Local dimensions of cultural participation. Ethnographic action research”, Warsaw University within a larger framework of a Ministry of Culture grant “Creating bottom-up culture”. In this project students and The Field Collective created an ethnoanimation project in the villages of Zaława and Cukrówka in Poland. They reflected upon them by putting them on an “animation zip” diagram according to the level of cohesion between animation and ethnography in their projects. The “animation zip” as an useful tool that may be interpreted inthe context of “best practices” of culture animation defined by National Culture Centre to define typical features of ethnoanimation practices. In this text the author tries to answer the question–what makes an ethnoanimation project most effective.